How Gas Meter Manufacturers Can Avoid Price Wars Under Demand Monopoly Conditions - Liu, Qinghua; Huang, Jie (International Journal of Global Economics and Management, 2024)
Gas meters are measuring tools that are crucial to people's livelihoods. In recent years, with the comprehensive popularization of the digital economy, gas services have also entered the era of IoT intelligence. The demand for smart gas meters continues to be strong, but gas meter manufacturers are deeply mired in price wars. This article uses industry analysis methods to analyze the reasons, phenomena, and impacts of price wars in the gas meter industry from both the supply and demand sides. Combined with practical cases of enterprises, basic strategies to avoid price wars are proposed.